Numerical simulation of radiation damage on the device performance of GaAs MESFETs - Beddiafia, Y.; Saadounea, A.; Dehimib, L. (Science des matériaux (Laboratoire LARHYSS); Vol. 1 (2014): Science des matériaux, 2014)
In this work, the effect of the radiation on the current-voltage characteristics of device GaAs metal Schottky field effect transistors (MESFET) at room temperature is investigated. Numerical Simulation tuned by means of a physics based device simulator. When the substrate of this transistor is subjected to radiations, structural defects, which are created, have undesirable effects and can degrade the performance of the transistors. These defects appear like deep traps. Results showed that in the presence of donor traps the current-voltage characteristics increases.However,acceptor traps have a significant effect on the current-voltage characteristics. In the presence of acceptor traps, the space charge zone in the channel increases, hence, reduces the current drain.